2009
DOI: 10.1093/pcp/pcp013
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Aluminum on the Actin Cytoskeleton and Brefeldin A-Sensitive Vesicle Recycling in Root Apex Cells of Two Maize Varieties Differing in Root Elongation Rate and Aluminum Tolerance

Abstract: A relationship between aluminum (Al) toxicity, endocytosis, endosomes and vesicle recycling in the root transition zone has recently been demonstrated. Here the importance of filamentous actin (F-actin)-based vesicle trafficking for Al tolerance has been investigating in maize varieties differing in their Al sensitivities. More Al was internalized into root tip cells of the Al-sensitive variety 16x36 than in the Al-tolerant variety Cateto. The actin cytoskeleton and vesicle trafficking were primary targets for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 61 publications
5
41
0
1
Order By: Relevance
“…For instance, (1) there is not so much nucleolar material released from nuclei into cytoplasm in Helianthus annuus, and (2) Al toxicity on the nucleoli in root tip cells of A. cepa and V. faba is stronger than one in H. annuus. Amenós et al (2009) indicated that Al was localized inside the nucleoli of root tip cells of Al sensitive maize. The evidence from the present work shows that once many particles of argyrophilic proteins are scattered in the nuclei, root growth in H. annuus can be inhibited, and once a large amount of nucleolar material is extruded from the nucleus into the cytoplasm, root growth is seriously inhibited or the seedlings died.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, (1) there is not so much nucleolar material released from nuclei into cytoplasm in Helianthus annuus, and (2) Al toxicity on the nucleoli in root tip cells of A. cepa and V. faba is stronger than one in H. annuus. Amenós et al (2009) indicated that Al was localized inside the nucleoli of root tip cells of Al sensitive maize. The evidence from the present work shows that once many particles of argyrophilic proteins are scattered in the nuclei, root growth in H. annuus can be inhibited, and once a large amount of nucleolar material is extruded from the nucleus into the cytoplasm, root growth is seriously inhibited or the seedlings died.…”
Section: Discussionmentioning
confidence: 99%
“…Gradually the nucleolar material was extruded from the nucleus into the cytoplasm. This may be explained by the effects of Cd 2+ treatment on proteins, causing the NPC to lose selectivity (Amenós et al, 2009;Qin et al, 2010). Finally the material occurred throughout the cytoplasm, eventually leading to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…51 A number of experimental data globally indicates that the transition zone of the root may be considered as a sort of sensory center, enabling the root apex to continuously monitor environment parameters and to trigger appropriate responses. [51][52][53][54][55][56][57][58][59][60][61][62][63] Future studies will be needed to deepen the role of this unique root zone in translating the external stimuli in motoric responses.…”
Section: The Root Transition Zonementioning
confidence: 99%